Hematopoietic Cell Transplantation for Tolerance Induction: Animal Models to Clinical Trials - Sykes, Megan (2009)
The induction of donor-specific immune tolerance is the “holy grail” oftransplantation, as it would avoid the toxicities of chronic immunosuppressive therapies while preventing acute and chronic graft rejection. A large number of approaches to tolerance induction have been described in the experimental literature, but only hematopoietic cell transplantation has shown preliminary success for intentional tolerance induction in pilot clinical trials. In this review, I summarize the conditions that allow progress to be made in moving strategies for tolerance induction from the bench to the bedside and discuss the mechanisms by which tolerance may be achieved via hematopoietic cell transplantation.